2021
DOI: 10.1016/j.jmig.2021.04.010
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Validity Evidence for the Fundamentals of Laparoscopic Surgery Examination in Gynecology

Abstract: Objective: The Fundamentals in Laparoscopic Surgery (FLS) examination is designed to test laparoscopic surgery skills. Our aim for this systematic review was to examine validity evidence supporting or refuting the FLS examination specifically as a high-stakes summative assessment tool in gynecology. Data Sources: The data sources were PubMed, MEDLINE, Embase, and Scopus. Methods of Study Selection: The study eligibility criterion was the subject of the FLS examination as an assessment tool in gynecology. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We know, for example, that in the Fundamentals of Laparoscopic Surgery (FLS) the passing rate was set at 10 times in total. 14,15 It is anticipated that these default benchmarks will initially be used "as is" by institutions, until further studies suggest updates are necessary. However, current simulation software does allow Institutions to modify these benchmarks as well as the pro ciency criteria, such as number of required passes.…”
Section: Discussionmentioning
confidence: 99%
“…We know, for example, that in the Fundamentals of Laparoscopic Surgery (FLS) the passing rate was set at 10 times in total. 14,15 It is anticipated that these default benchmarks will initially be used "as is" by institutions, until further studies suggest updates are necessary. However, current simulation software does allow Institutions to modify these benchmarks as well as the pro ciency criteria, such as number of required passes.…”
Section: Discussionmentioning
confidence: 99%
“…To address this gap in training, we sought to create an easy-to-set-up simulator that would allow learners to practice specific parts of a procedure and hold their attention for extended periods of time. Our original concept was an analogue of the Fundamentals of Laparoscopic Surgery 15 , 16 or a set of nonclinical tasks that would allow one to practice the psychomotor skills used during ultrasound-guided invasive procedures. We named this training system the Fundamentals of Ultrasound Needle Guided Interventions, or FUNGI for short.…”
Section: Methodsmentioning
confidence: 99%
“…Fundamentals in Laparoscopic surgery (FLS) has been widely used to test laparoscopic surgical skills and is a prerequisite for board eligibility in general surgery and obstetrics and gynaecology (American Board of Obstetrics and Gynecology). A recent systematic review examining the validity evidence of FLS examination has shown to be mixed or lacking (Lerner et al, 2021). Another example is the Objective Structured Clinical Examination (OSCE) and Objective Structured Assessment of Technical Skills (OSATs) which have been in use for some time now (Faulkner et al, 1996;Martin et al, 1997;Regehr et al, 1998).…”
Section: Introductionmentioning
confidence: 99%